How to Decide the Number of Gait Cycles in Different Low-Pass Filters to Extract Motor Modules by Non-negative Matrix Factorization During Walking in Chronic Post-stroke Patients - Chujo, Yuta; Mori, Kimihiko; Kitawaki, Tomoki; Wakida, Masanori; Noda, Tomoyuki; Hase, Kimitaka (Frontiers in Human Neuroscience, 2022)
The motor modules during human walking are identified using non-negative matrix factorization (NNMF) from surface electromyography (EMG) signals. The extraction of the motor modules in healthy participants is affected by the change in pre-processing of EMG signals, such as low-pass filters (LPFs); however, the effect of different pre-processing methods, such as the number of necessary gait cycles in post-stroke patients with varying steps, remains unknown. We aimed to specify that the number of gait cycles influenced the motor modules extracted in consideration of LPFs in post-stroke patients. Ten chronic post-stroke patients walked at a self-selected speed on an overground walkway, while EMG signals were recorded from eight muscles of paretic lower limb. To verify the number of gait cycles, five gait cycle conditions were set, namely: 25 (reference condition), 20, 15, 10, and 5 gate cycles with three LPFs (4, 10, and 15 Hz). First, the number of modules, variability accounted for (VAF), and muscle weightings extracted by the NNMF algorithm were compared between the conditions. Next, a modified NNMF algorithm, in which the activation timing profiles among different gait cycles were unified, was performed to compare the muscle weightings more robustly between gait cycles. The number of motor modules was not significantly different, regardless of the gait cycles. The difference in VAF and muscle weightings in the different gait cycles decreased with the LPF of 4Hz. Muscle weightings in 15 gait cycles or less were significantly different from those in 25 gait cycles using the modified NNMF. Therefore, we concluded that the variability extracted motor modules by different gait cycles was suppressed with lower LPFs; however, 20 gait cycles were needed for more representative extraction of motor modules during walking in post-stroke patients.